The Role of Self-Compassion in the Lived Experiences of Service Providers Working in Canadian Cancer Support Programs - Karimah Kiranda; Unnati Modi; Danielle Silva; Cristina Alexandra Guerrero; Tina Lackner (Journal of Innovation in Polytechnic Education)
Working and providing cancer support services is both challenging and rewarding, yet the lived experiences of the personnel providing such services remain overlooked. It is vital to address the experiences of service providers to better understand the nature of their work and how it may impact their well-being. This paper explores the lived experiences of cancer support service providers, focusing on how they conceptualize and practice self-compassion in their workplace. A qualitative approach centred on phenomenological hermeneutics was utilized to collect in-depth interview data from service providers working in cancer support centres across southwestern Ontario, Canada. The research team used descriptive and narrative analysis to analyze the interview data and produced the following four themes: 1) acknowledging personal limits as a form of self-compassion; 2) organizational support; 3) emotional environment; and 4) prioritized self-care. Recommendations include more comprehensive support systems for service providers, especially if they may be experiencing secondary trauma or compassion fatigue. The findings gleaned from the service providers contribute valuable considerations for both the cancer care workplace and post-secondary institutions. While the findings provide real-life examples of effective support for service providers in the workplace, they also provide important considerations for post-secondary programming that include strategies for balancing empathetic service delivery with exercising self-compassion.